2016
DOI: 10.1177/1049909115625612
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scale to Assess Physician Advance Care Planning Self-Efficacy

Abstract: The final ACP-SE scale included 17 items and demonstrated high internal consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
0
31
1
Order By: Relevance
“…The advanced care planning (ACP) process includes ongoing discussions among health-care providers, patients, and their families about disease pathways, treatment options, patient goals, values, and preferences. 1 The premise of ACP formulation is that patients have clear consciousness and obtain information about prognosis and ACP measures. The goal of ACP is to help patients get medical care that is consistent with their values, goals, and preferences during serious and chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…The advanced care planning (ACP) process includes ongoing discussions among health-care providers, patients, and their families about disease pathways, treatment options, patient goals, values, and preferences. 1 The premise of ACP formulation is that patients have clear consciousness and obtain information about prognosis and ACP measures. The goal of ACP is to help patients get medical care that is consistent with their values, goals, and preferences during serious and chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, we adapted, developed and preliminarily tested a survey to measure knowledge, selfefficacy, attitudes and practices ourselves. However, the self-efficacy scale from Baughman et al, published in 2016, showed high internal consistency and some evidence of convergent, known groups, and predictive validity in family physicians and might be used in the future for similar research, after being tested in this particular population [44]. In addition, responses of staff and volunteers of intervention groups may be affected by their knowledge of their allocation because blinding will not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…40 There is compelling evidence that knowing the person's treatment preferences could reduce the burden on surrogates, 41 prevent burdensome interventions of questionable benefit near end of life, 42 and reduce inappropriate hospital admissions and health-care costs for persons with cognitive impairment and dementia. 2,3 While some physicians prefer to discuss ACP when patients initiate the conversation, 26,43 lack of patient and family knowledge about ACP may prevent them from initiating the conversation. Education for patients and families about ACP within the context of dementia is an important role that PCCMCs can assume.…”
Section: Discussionmentioning
confidence: 99%
“…While some physicians prefer to discuss ACP when patients initiate the conversation, 26,43 lack of patient and family knowledge about ACP may prevent them from initiating the conversation. Education for patients and families about ACP within the context of dementia is an important role that PCCMCs can assume.…”
Section: Discussionmentioning
confidence: 99%